Multi-centre prospective cohort study of diaphragmatic defect phenotype and repair in neonates with congenital diaphragmatic hernia: 'The Defect Study'. Issue 1 (2nd February 2022) - Eastwood, Mary Patrice; Harwood, Rachel; Rhodes, Hannah; Bethell, George Stephen; Bradnock, Timothy J; Hall, Nigel J
Abstract: Defect size and closure technique in neonates with congenital diaphragmatic hernia (CDH) has long-term consequences for morbidity in survivors. Although subjective operative reporting of the defect size has been standardized, objective evaluation is lacking. There is no reported optimum closure technique related to the size and position of the diaphragmatic defect. We aim to objectively describe diaphragmatic defects and repair methods, at the time of neonatal CDH repair, through a prospective multi-centre service evaluation project. We will evaluate all neonates born with CDH surviving to diaphragmatic repair. All specialist paediatric surgical centres in the UK, Ireland and New Zealand will be invited to participate. Non-identifiable patient data will be collected over a 24-month period using a REDCap database. Diaphragmatic defects and hemidiaphragm measurements will be recorded intra-operatively alongside standardized defect reporting. Closure technique and 1-year outcomes will be captured. Demographics and peri-operative data will be reported as median (interquartile range), mean (standard deviation) or categorical variables. Defect measurement will be calculated as an ellipse with area displayed as a histogram. Patch usage will be compared to the defect area using univariate logistic regression analysis. Univariate logistic regression analysis will also be used to assess for the association between peri-operative variables and complications. Where possible, a multi-variate regression analysis will be performed. Centres will register the project as service evaluation at each participating hospital site. The results will be submitted to an international peer reviewed journal and will be disseminated via appropriate international forums and through patient support networks (CDH-UK).